2021
DOI: 10.1007/s00500-021-06032-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical approach for differential-difference equations having layer behaviour with small or large delay using non-polynomial spline

Abstract: A numerical approach is suggested for the layer behaviour differential-difference equations with small and large delays in the differentiated term. Using the non-polynomial spline, the numerical scheme is derived. The discretization equation is constructed using the first order derivative continuity at non-polynomial spline internal mesh points. A fitting parameter is introduced into the scheme with the help of the singular perturbation theory to minimize the error in the solution. The maximum errors in the so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The solution's layer behaviour is preserved, and precise results are obtained when compared to the perturbation parameter; the shift parameter is smaller [22,23]. However, if δðεÞ is of order OðεÞ, the solution's layer behaviour is no longer well-preserved, and oscillations becomes visible.…”
Section: Numerical Approach With Fitting Parameter For Large Delaymentioning
confidence: 99%
See 2 more Smart Citations
“…The solution's layer behaviour is preserved, and precise results are obtained when compared to the perturbation parameter; the shift parameter is smaller [22,23]. However, if δðεÞ is of order OðεÞ, the solution's layer behaviour is no longer well-preserved, and oscillations becomes visible.…”
Section: Numerical Approach With Fitting Parameter For Large Delaymentioning
confidence: 99%
“…With the motivation of the numerical scheme derived in the manuscript titled "Numerical Approach for Differential-Difference Equations having Layer Behaviour with Small or Large Delay using Non-Polynomial Spline," https://assets .researchsquare.com/files/rs-261904/v1_covered.pdf (Ref. [23]), we have derived a scheme for the problem having large delay in this manuscript. We thank the reviewers for their constructive comments/suggestions to strengthen the manuscript.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar and Rao [24] considered a stabilized central difference method by modifying the error terms for the boundary value problem (BVP) of singularly perturbed differential equations with a large delay. The work in [25] suggested a non polynomial spline method for solving this type of problems. An almost first order convergent finite difference scheme by using piecewise Shishkin type mesh is presented in [26] and an exponentially fitted finite difference method is suggested in [27] to tackle the problem.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [9] used a nonpolynomial spline to develop a numerical solution for a DDEs having layer with a small and large delay in the differentiated terms. Using domain decomposition, the authors of [10] suggested a mixed difference technique to solve DDEs with mixed shifts.…”
Section: Introductionmentioning
confidence: 99%